Manufacturing surface technology : surface integrity & functional performance - Griffiths, Brian, 1945- (Penton, 2001)
The first title in the ""Manufacturing Engineering Modular"" series, the publication of this book marks recognition of the effect of surface finish obtained in manufacture (""surface integrity"") on the functional performance of product, in terms of such factors as fatigue, corrosion and strength. It is a concise work, intended chiefly for undergraduate and postgraduate students, which should also provide useful material for the professional manufacturing engineer.